Haemoglobin, albumin, lymphocyte, and platelet score as an independent predictor for renal prognosis in IgA nephropathy - Yuan, Yuan; Liang, Xiaoli; He, Minhui; Wu, Yufan; Jiang, Xue (Frontiers in Endocrinology, 2024)
Objective: The haemoglobin, albumin, lymphocyte, and platelet (HALP) score, a convenient and composite laboratory biomarker, can reflect inflammation and systemic nutritional status. This study was performed to investigate the effect of the HALP score on the prognosis of patients with IgA nephropathy (IgAN).This is a retrospective single centre study that enrolled 895 biopsy-confirmed IgAN patients from June 2019 to June 2022 who were followed for more than 1 year. Kaplan-Meier curves and Cox regression analyses were performed to determine the relationship between HALP and adverse outcomes. The restricted cubic splines was used to identify the possible associations. The optimal cut-off value of HALP for renal poor outcome was identified by the area under the receiver operating characteristic curve (AUC).A total of 895 patients finally participated in the study and were divided into three groups (tertial 1-3) according to the baseline HALP score. More severe clinicopathologic features were observed in the lower HALP group, and Kaplan-Meier analysis showed patients in tertial 1 had a higher risk of kidney failure than the other groups (log-rank=11.02, P= 0.004). Multivariate Cox regression revealed that HALP score was an independent risk factor for renal prognosis in IgAN (adjusted HR: 0.967, 95% CI: 0.945-0.990, P = 0.006). The results of subgroup analysis suggested that HALP was more important in patients under the age of 50, BMI≤23.9 and eGFR≤90 mL/min/1.73 m2. The best cut-off HALP for renal survival was 38.83, sensitivity 72.1%, and specificity 55.9% (AUC: 0.662). Patients were further grouped according to HALP cut-off values and propensity matched.Multivariate Cox regression analysis revealed that HALP remained an independent predictor of IgAN in the matched cohort (HR 0.222, CI: 0.084-0.588, P=0.002).HALP is a novel and potent composite parameter to predict kidney outcome in patients with IgAN.